Analysis of Circulating Catestatin in Early Pregnancy: A Preliminary Investigation - Zdenka Sunjic Lovric; Jasminka Resic Karara; Bianka Mimica; Marko Kumric; Daniela Supe-Domic; Roko Santic; Josko Bozic (Biomedicines)
Background: During pregnancy, significant cardiovascular changes occur to accommodate fetal growth, and catestatin may play a role in these changes. Evidence suggests that catestatin, a pleiotropic sympathoinhibitory peptide, is involved in multiple cardiovascular pathologies, including hypertensive disorders. The objective of this study was to compare serum catestatin levels between first-trimester pregnant women and non-pregnant women, aiming to investigate catestatin’s role in blood pressure regulation during early pregnancy. Methods: This cross-sectional study included 72 first-trimester pregnant women and 57 age-matched non-pregnant controls, all without known cardiovascular or metabolic disorders. Results: Serum catestatin concentrations were significantly higher in pregnant women compared to controls (12.4 (9.9–21.2) ng/mL vs. 7.1 (4.5–10.9) ng/mL, p < 0.001). However, there was no significant difference in serum catestatin levels between those with a normal and abnormal uterine artery pulsatility index (17.8 (8.3-22.3) ng/mL vs. 12.5 (9.9–22.4) ng/mL, p = 0.962). Similarly, catestatin concentrations did not significantly differ between primiparous and multiparous women (14.0 (11.5–22.4) ng/mL vs. 10.7 (8.8–19.0) ng/mL). A positive correlation was observed between systolic blood pressure and serum catestatin levels in the control group (r = 0.335, p = 0.011) but not in pregnant women. Conclusions: Research on catestatin in pregnancy is still in its early stages, necessitating further studies to fully elucidate its roles and potential therapeutic applications.